Are human resource managers with good listening competency more likely to avoid job burnout? - Yanqing Wang; Hong Chen (BMC Public Health, 2022)
Abstract Background Listening is an important responsibilities of human resource managers, whether it will bring role stress to human resource managers, or lead to the risk of job burnout. This study aims to analyze the impact of listening competency on job burnout among human resource managers, and examine the mediating effect of role stress. Methods This study adopted a cross-sectional method to randomly select 500 human resource managers from China’s top ten human resource management cities to conduct an online questionnaire survey, and 232 valid samples were obtained. Descriptive statistical and one-way ANOVA were used to explore the status of job burnout among human resource managers in China. Correlation analysis, multiple linear regression and mediating effect analysis were employed to test the relationship between listening competency and job burnout, as well as the mediating effect of role stress. Results (1) 34.5% of the respondents reported mild burnout, while 3.0% respondents showed serious burnout. Emotional exhaustion was the most serious. (2) Those are good at listening could easily avoid job burnout. Among them, listening skills were conducive to reducing the degree of depersonalization of human resource managers, and empathy was more conducive to improving their personal sense of accomplishment. (3) The role stress had a significant mediating role in the relationship between listening competency and job burnout. Which means that listening competency can avoid job burnout by reducing role stress of human resource managers. Conclusions This study revealed the current situation of job burnout among human resource managers in China, and explored the influence of listening competency on job burnout. This study enriched the research content of job burnout, and provided references for preventing and intervening job burnout of human resource managers.